Patogenesis and management of Graves’ ophthalmopathy - Wierzbowska, Joanna; Stankiewicz, Andrzej (Klinika Oczna / Acta Ophthalmologica Polonica, 2002)
The most recent hypothesis on pathogenesis of Graves' Ophthalmopathy (GO) and short characteristics of the disease was presented. Emphasis was placed on the neccesity of coordinated treatment of the thyroid dysfunction and ophthalmopathy. Management of hyperthyroidism and Graves' ophthalmopathy, including the latest methods was described